If X has the Poisson distribution with parameter L (lambda), show that:
E[X * (X - 1) * (X - 2) ... (X - k)] = L^(k+1), for k = 0, 1, 2...
I'm assuming all the X's are independent, in which case it's E[X] * E[X-1] ... E[X-k] = L * (L - 1) ... (L - k). Which doesn't equal L^(k+1).
If the X's aren't independent, it turns into a game of guess the value of the infinite sum. Ew.
E[X * (X - 1) * (X - 2) ... (X - k)] = L^(k+1), for k = 0, 1, 2...
I'm assuming all the X's are independent, in which case it's E[X] * E[X-1] ... E[X-k] = L * (L - 1) ... (L - k). Which doesn't equal L^(k+1).
If the X's aren't independent, it turns into a game of guess the value of the infinite sum. Ew.
Comment